Effects of fermented rice husk powder on growth performance, rumen fermentation, and rumen microbial communities in fattening Hu sheep - Cheng, Yanming; Zhang, Han; Zhang, Jiawei; Duan, Hongwei; Yin, Yuyang; Li, Yufeng; Mao, Shengyong (Frontiers in Veterinary Science, 2024)
IntroductionThis study aimed to examine the effects of fermented rice husk powder feed on growth performance, apparent nutrient digestibility, and rumen microbial communities in fattening Hu sheep.MethodsTwenty-one male Hu sheep with similar body weights (32.68 ± 1.59 kg) were randomly assigned to three groups: a control group (CON) receiving a TMR with soybean straw, a rice husk powder group (RH), and a fermented rice husk powder group (FHR).ResultsThe results indicated that the FHR group exhibited a significant increase in ADG and FBW of Hu sheep compared to the other two groups (p < 0.05). The digestibility of CP and EE was significantly higher in the CON and FHR groups than in the RH group (p < 0.01). Furthermore, the digestibility of DM in the CON group was higher than in the FHR and RH groups (p < 0.01). The FHR group showed lower NDF and ADF digestibility compared to the CON group, but higher than the RH group (p < 0.05). Additionally, serum ALB and ALT levels in the CON group were elevated compared to those in the two groups (p < 0.05). The rumen concentrations of TVFA, butyrate, and valerate in the FHR group were significantly elevated compared to the other two groups (p < 0.05). At the genus level, the relative abundances of Rikenellaceae RC9 gut group, Succinimonas, UCG-010_norank, UCG-005, p-251-o5_norank, and Lachnospiraceae AC2044 group were significantly diminished in the FHR group compared to the CON group (p < 0.05). In contrast, the relative abundance of Succinivibrio was significantly higher (p < 0.05), while the abundances of Eubacterium coprostanoligenes group_norank and Quinella were significantly lower (p < 0.05) in the RH group compared to the CON group. Spearman correlation analysis revealed negative correlations between the Rikenellaceae RC9 gut group and propionate, butyrate, and TVFA, as well as between Prevotellaceae UCG-003 and both propionate and TVFA. Conversely, Ruminococcus showed a positive correlation with propionate and TVFA.DiscussionIn conclusion, replacing 15% of soybean straw with fermented rice husk powder feed modified the rumen microbiota and improved the growth performance of fattening Hu sheep.